SOCIAL MEDIA MARKETING; STRATEGI KOMUNIKASI BISNIS ERA DIGITAL (Studi Analisis Portal TaniFund.com) - Mellyan Mellyan (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2020)
The digital world with all its novelty brings changes in every field. This was triggered by the advent of internet technology. Various sectors adapt to the emergence of the technology, one of the business. At the previous two decades, business world is still prevalent using traditional methods, now the business world uses digital media, including social media in it for promotion and business development. Tanifund is a financial funding platform that focuses on agriculture, animal husbandry, and fisheries. It is interesting to study Tanifund because there are big differences in the era of digital agriculture that "move" agricultural land in the digital world and the traditional era which considers agriculture is a heavy work that is only done in open land. This research method uses qualitative research, library research with a descriptive analysis approach. The results of the research show Fanifund has utilized social media for business promotion and development, it's just not been implemented to the maximum. Maximizing the use of social media can increase the number of people who use tanifund. It takes several treatments and a solid team to move social media into media promotion and business development.